2020
DOI: 10.1002/aqc.3293
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution and population trends of the smalltail shark Carcharhinus porosus inferred from species distribution models and historical catch data

Abstract: Updated distribution ranges are crucial for conservation status assessments. Comprehensive analyses combining published literature and available data on historical catches and species distribution models (SDMs) are effective tools that could improve the prediction of more realistic scenarios for some species, especially those with limited information available and facing multiple threats. The present study aimed at generating an updated distribution for the smalltail shark Carcharhinus porosus, one of the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Additionally, the species likely spends its whole life cycle within the continental platform, but with a small degree of habitat partitioning between sexes and several different birthing grounds. Furthermore, recent analysis estimated that the Northern coast of South America (defined as the coastal extension between Guyana and Maranhão state) is actually the region with the smallest decline in catch probability along the species distribution (Feitosa et al, 2020). The last IUCN species assessment also considers this area as the center of abundance for this species (Lessa et al, 2006).…”
Section: Evaluation Of Nursery Criteria and Suggestions For Effectivementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the species likely spends its whole life cycle within the continental platform, but with a small degree of habitat partitioning between sexes and several different birthing grounds. Furthermore, recent analysis estimated that the Northern coast of South America (defined as the coastal extension between Guyana and Maranhão state) is actually the region with the smallest decline in catch probability along the species distribution (Feitosa et al, 2020). The last IUCN species assessment also considers this area as the center of abundance for this species (Lessa et al, 2006).…”
Section: Evaluation Of Nursery Criteria and Suggestions For Effectivementioning
confidence: 99%
“…Despite its small size (150 cm estimated maximum length), its life history traits make it easily susceptible to overfishing since its fecundity is low (average of 6 pups per gestation), the reproductive cycle is biannual, and both sexes reach sexual maturity with 6 years old (Lessa and Santana, 1998). It is highly associated to turbid and dynamic areas with mangrove rich coasts (Feitosa et al, 2020), and juveniles were consistently caught near estuaries in Maranhão state's coast (Menni and Lessa, 1998). Nevertheless, its habitat use patterns are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, C. porosus original area of distribution ranged from the northern coast to Cananeia beach in São Paulo, Southeastern Brazil [18][19][20]. Recent studies demonstrated that this occurrence pattern has changed dramatically with a significant decrease in the species' distribution area throughout Brazil's coast [21][22][23]. These declines caused by possible local extinctions restricted C. porosus occurrence to the northern coast of Brazil between Maranhão and Amapá states [21].…”
Section: Introductionmentioning
confidence: 99%
“…This area is considered its global center of abundance for the high proportion of individuals caught when compared to other regions where it occurs [24]. Recent data estimates show that the Amazon coast is likely the most important area for its conservation along its geographical distribution [23]. Notwithstanding, it was the dominant species of shark landed during the 1980s and 1990s in the Brazilian Northern coast (BNC), but it is now only the third most caught shark species in the region [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation